PROPRIOCEPTION AND PROPRIOCEPTIVE EXERCISES - Ahmet Yılmaz,; Haydar Gök, (Archives of Rheumatology, 2006)
The ability that transmit the sensation of body position, perception and interpretation of this data and giving an conscious or unconscious reaction resulting in approximate posture and movement is called proprioception. The impulses that come from skin receptors, joints, muscles and tendons are perceived and interpreted by the proprioceptor regions of the central nervous system which in turn sends the required excitatory or inhibitory efferent responses. Repetitive soft tissue injury, osteoarthritis and low back pain are frequently associated with propri oceptive weakness and it is possible to measure this weakness by evaluating the conscious submodalities of proprioception. Proprioceptive weakness can be improved with balance training, kinetic chain exercises, sport specific exercises as well as exercises focused on low back and shoulder. (Rheumatism 2006; 21: 23-6)